PENGARUH KOMPETENSI, AKUNTABILITAS DAN TRANSPARANSI TERHADAP EFEKTIVITAS PENGELOLAAN DANA DESA - Ni Luh Putu Hindrayani; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
The effectiveness of village fund management is important for the implementation of good village governance. Various factors that can have an impact on the effectiveness of village fund management include competence, accountability and transparency. This study aims to determine the effect of competence, accountability and transparency on the effectiveness of village fund management in Kintamani District, Bangli Regency. The research sample was 48 villages in Kintamani District and the number of respondents was 144 people. Purposive sampling was used as a method of determining the sample and collecting data by means of a questionnaire. Data analysis was carried out by descriptive statistical analysis, validity test, reliability test, classical assumption test, F test, determination coefficient test and t test and multiple linear regression analysis.